When the solution is on the doorstep:: better solving performance, but diminished aha! experience for chess experts on the mutilated checkerboard problem - Bilalić, Merim; Graf, Mario; Vaci, Nemanja; Danek, Amory H. (Cognitive science, 2019)
Insight problems are difficult because the initially activated knowledge hinders successful solving. The crucial information needed for a solution is often so far removed that gaining access to it through restructuring leads to the subjective experience of “Aha!”. Although this assumption is shared by most insight theories, there is little empirical evidence for the connection between the necessity of restructuring an incorrect problem representation and the Aha! experience. Here, we demonstrate a rare case where previous knowledge facilitates the solving of insight problems but reduces the accompanying Aha! experience. Chess players were more successful than non-chess players at solving the mutilated checkerboard insight problem, which requires retrieval of chess-related information about the color of the squares. Their success came at a price, since they reported a diminished Aha! experience compared to controls. Chess players’ problem-solving ability was confined to that particular problem, since they struggled to a similar degree to non-chess players to solve another insight problem (the eight-coin problem), which does not require chess-related information for a solution. Here, chess players and non-chess players experienced the same degree of insight.
Gesehen am 21.01.2020